1996
DOI: 10.1021/ja961305+
|View full text |Cite
|
Sign up to set email alerts
|

Exchange and Double-Exchange Phenomena in Linear Homo- and Heterotrinuclear Nickel(II,III,IV) Complexes Containing Six μ2-Phenolato or μ2-Thiophenolato Bridging Ligands

Abstract: A series of homo- and heterotrinuclear complexes containing three face-sharing octahedra has been synthesized by using the pendent arm macrocyclic ligands 1,4,7-tris(3,5-dimethyl-2-hydroxybenzyl)-1,4,7-triazacyclononane, L0H3, and 1,4,7-tris(4-tert-butyl-2-mercaptobenzyl)-1,4,7-triazacyclononane, LH3:  [{L0NiII}2NiII] (1) and [{LCoIII}2CoIII](PF6)3 (2); [{LCoIII}2Ni] n + (n = 2 (3), 3 (4), 4 (5)); [{LNi}2CoIII] n + (n = 1 (6), 2 (7), 3 (8)) and its linkage isomers [{LNi}Ni{CoIIIL}] n + (n = 1 (9), 2 (10), 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 60 publications
6
74
2
Order By: Relevance
“…[12] We anticipate a more detailed study of the electronic spin systems of 3b and 4b by magnetic susceptibility measurements. [10a] were prepared as previously described.…”
Section: Electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…[12] We anticipate a more detailed study of the electronic spin systems of 3b and 4b by magnetic susceptibility measurements. [10a] were prepared as previously described.…”
Section: Electrochemistrymentioning
confidence: 99%
“…[12,13] to many other N 2 Ni(µ 2 -SR) 2 NiN 2 type complexes, the We now present the synthesis, structural, spectral, and amine-thiolate complex 2a was shown to readily react with redox properties of the selenium analogs of 3a,b. another one equivalent of 1a to afford the dinuclear, facesharing bioctahedral complex 3a.…”
Section: Introductionmentioning
confidence: 98%
“…We have shown previously [10] that this compound can be oxidized by two successive one-electron steps to give a paramagnetic Ni III and a diamagnetic Ni IV complex. Figure 3 shows the EPR spectra of 1 and 2 in CH 3 CN solution and their simulations.…”
Section: Methodsmentioning
confidence: 93%
“…[8] In contrast, no examples of heterometallic vanadium/cobalt or vanadium/nickel thiolato complexes were found in the literature. A series of trinuclear metal complexes of the type [LMMЈML] n+ with L = 1,4,7-tris(4-tertbutyl-2-mercaptobenzyl)-1,4,7-triazacyclononane like [LCoNiCoL] n+ (n = 2-4), [LNiCoNiL] n+ (n = 1-3), [9] [LFeNiFeL] n+ (n = 2-4), [10] [LFeMFeL] n+ (M = Cr, Co; n = 1-3) [11] and [LFeMFeL] n+ (M = Ge, Sn; n = 2,3) [12] have been synthesised and characterised with respect to their magnetic exchange properties. It was shown that in these compounds the mechanism of spin coupling cannot be described exclusively in terms of the classical superexchange mechanisms but rather spin-dependent delocalisation by means of double exchange mechanisms [9] had to be invoked.…”
Section: Introductionmentioning
confidence: 99%